Exposure to Computer Work and Prevalence of Musculoskeletal Symptoms Among University Employees: A Cross-Sectional Study. - Stanam, Aditya; Golla, Vijay; Vasa, Shradha J.; Taylor, Ritchie D. (Journal of Environmental Health, 2019)
University faculty and staff, like other kinds of computer users, are exposed daily to long hours of computer work and thereby can be at risk of musculoskeletal symptoms (MSS). The objectives of this study were to 1) assess computer use-related exposures, 2) estimate the prevalence of MSS, and 3) analyze the relationship between ergonomic exposures and MSS among university faculty and staff. Questionnaire administration and ergonomic assessment were conducted among 51 faculty and staff via office visits. The majority of participants (approximately 70%) were exposed for prolonged time periods (i.e., >4 hr/day) with reduced rest breaks during their computer work. More than 75% of the participants had their keypads at a slope >10 degrees. Among all the MSS studied, lower back pain (60%), neck pain (58%), and shoulder pain (49%) were the top three prevalent MSS. Participants who worked >4 hr/day were significantly associated with neck pain (p = .036) and low back pain (p = .043). Also, the risk of low back pain decreased (odds ratio = 0.7) with an increase in rest breaks. Computer work for prolonged hours with fewer breaks might enhance the risk of MSS. Further research is needed to validate our findings.